Relación entre la pobreza monetaria con el nivel de empleo y el crecimiento económico en el departamento de Loreto, periodo 2008 - 2019 - Nube Yactayo, José Manuel (2022)
The research work determines the influence that the level of employment and economic growth exert on the percentage of inhabitants of the department of Loreto who are in a situation of monetary poverty, in the period 2008-2019. Monetary poverty is defined as the pecuniary inability on the part of the inhabitants to acquire the basic basket of food and not the food necessary to satisfy primary needs. The research work is of a Quantitative type, Descriptive-Correlational level and Non-experimental design; Therefore, once the information on the level of income of families, employment and economic activities in the department of Loreto had been collected, the univariate analysis and application of the OLS methodology was carried out. After obtaining and discussing the results, it is concluded that during the analyzed period monetary poverty in Loreto was reduced by -35.34%, the employment level variable has a strong and significant negative correlation with the monetary poverty variable (r = -0.817); Otherwise, economic growth does not present any relationship with monetary poverty in the analyzed period (r = 0.022). When jointly analyzing the independent variables level of employment and economic growth with the dependent variable monetary poverty, it is verified that only the level of employment is a determinant of monetary poverty in Loreto (p> t = 0.001), and that a growth of one point percentage in the level of employment generates a reduction of -13.42% of monetary poverty.